Transhepatic-intrahepatic branches of the portal vein catheterization for ex vivo liver resection and autotransplantation: Two case reports of novel approach to perfuse the liver. Issue 11 (March 2019) - Kong, Junjie; Shen, Shu; Yang, Xianwei; Wang, Wentao
Abstract: Rationale: There has been increased use of ex vivo liver resection and autotransplantation (ERAT) for treatment of end-stage hepatic alveolar echinococcosis (HAE). Rapid perfusion of the autograft in bench resection is always required to reduce the warm ischemia time (WIT) and to protect the function of the remnant liver. Nevertheless, the severe invasion of the portal hepatis sometimes makes it impossible to find a usable inflow rapidly and the process of perfusion could be delayed. Patient concerns: Two patients diagnosed with end-stage HAE combined with severe portal hepatis invasion were selected to undergo ERAT at our center. Diagnosis: Besides the large HAE lesions, the CT imaging of patient 1 showed that part of the intra- and extrahepatic portal vein (PV) had disappeared. Patient 2 had severe invasion of both of the right and left branches of the PV. Interventions: We introduced a new approach for perfusing the liver in ERAT using transhepatic-intrahepatic branches of the PV catheterization. Afterward, ERAT was successfully performed. Outcomes: For patient 1, the WIT was 2 minutes and the cold ischemia time (CIT) was 296 minutes. For patient 2, the WIT was 2 minutes and the CIT was 374 minutes. Patient 1 suffered stenosis of the common bile duct on postoperative day 14, and patient 2 recovered uneventfully. Both of the 2 patients were discharged from the hospital with normal laboratory values on postoperative day 31 and 15, respectively. The laboratory values for both patients at recent follow-up were normal. Lessons: Transhepatic-intrahepatic branches of the PV catheterization is useful for decreasing WIT and facilitating the management of ERAT. It is a useful technical variant that could be used in ERAT for treating patients with severe portal hepatis invasion. Abstract : Supplemental Digital Content is available in the text